Application Principle Diversity in Honorimplementation of Worship for Every Citizen Asdraft Resilience National - Arza Ratu Zahra (International Journal of Students Education, 2024)
Diversity own role important in carry out worship for inhabitant country. The aim of this research is to strengthen the sense of tolerance that originates from the intention and spirit of appreciating and respecting others with the belief that all man on in essence the same and equivalent. Research This nature literature review this research is a summary of the author’s thoughts taken from several sources references. Results research this very push creation public which each other respect and harmony, despite differences in culture, religion and belief. By because that, conclusion from journal this is prevent gap in diversity is very important, because Indonesia recognizes the existence of six religions different. Because matter that important for embed principle and idea resilience national to prevent the gap between life and state.